How Sudden, Intense Energetic Electron Enhancements Correlate With the Innermost Plasmapause Locations Under Various Solar Wind Drivers and Geomagnetic Conditions. Issue 11 (26th November 2019) - Khoo, L.‐Y.; Li, X.; Zhao, H.; Chu, X.; Xiang, Z.; Zhang, K.
Abstract: In this report, the relationship between innermost plasmapause locations (Lpp) and initial electron enhancements during both storm and nonstorm ( Dst > −30 nT) periods are examined using data from the Van Allen Probes. The geomagnetic storms are classified into coronal mass ejection (CME)‐driven and corotating interaction region (CIR)‐driven storms to explore their influences on the initial electron enhancements, respectively. We also study nonstorm time electron enhancements and observe frequent, sudden (within two consecutive orbital passes) <400‐keV electron enhancements during quiet periods. Our analysis reveals an incredibly cohesive observation that holds regardless of electron energies (~30 keV–2.5 MeV) or geomagnetic conditions: the innermost Lpp is the innermost boundary of the initial energetic electron enhancements. Interestingly, the quantified energy‐dependent relationship of the sudden, intense energetic electron enhancements, with respect to the innermost Lpp, also exhibit a very similar trend during both storm and nonstorm periods. In summary, the goal of this report is to provide a comprehensive quantification of this consistent relationship under various geomagnetic conditions, which will also enable better forecast and specification of energetic electrons in the inner magnetosphere. Plain Language Summary: The state of the radiation belt is a balance of the acceleration, transport, and loss mechanisms. Previous studies have reported the close connection between the innermost plasmapause locations (Lpp) and the initial enhancements of relativistic electrons. Yet a comprehensive quantification of this correlation, particularly for tens and hundreds of keV electrons under different geomagnetic conditions, is still missing. Therefore, we work on this research front by investigating how the energetic electron (30 keV to 2.5 MeV) enhancements correlate with the innermost Lpp under both geomagnetic active and quiet periods. Based on our observations and analysis, we conclude that the initial electron enhancements are typically outside of the innermost Lpp regardless of the geomagnetic activity and solar wind drivers. This consistent relationship is crucial in advancing our understanding of outer belt electron enhancements and enabling better forecast and specification of energetic electrons in the inner magnetosphere. Key Points: Regardless of solar wind drivers (CME/CIR), initial electron enhancements are mostly outside of innermost plasmapause locations (Lpp) Electrons at lower energy occur closer to the innermost Lpp with a shorter time lag in both CME‐driven and CIR‐driven storms Sudden flux enhancements of <400‐keV electrons can occur during nonstorm times and are mostly found outside of the innermost Lpp